Doom and gloom versus optimism: An assessment of ocean-related U.S. science journalism (2001-2015). (May 2018) - Johns, Lisa N.; Jacquet, Jennifer
Highlights: To test concerns that the state of the oceans is represented in an overly negative way by the U.S. media, 169 articles in mainstream U.S. newspapers reporting on ocean science were analyzed. Doom and gloom language was identified in 10% of all articles, while optimistic language was present in 27%. Nearly half (45%) of all U.S. articles on ocean health issues mentioned potential solutions to the problems described. Abstract: In recent years, some scientists have expressed concern about the negative representation of the state of the oceans in the media. To examine this concern empirically, we analyzed the content of 169 articles in mainstream U.S. newspapers covering ocean-related research between 2001 and 2015. Content was categorized according to main issue, basis of evidence, causal attribution, presence of solutions and uncertainty, and coded for doom and gloom and optimistic language. Science journalism about ocean issues most commonly addressed climate change and the status of ocean species or populations. The majority of articles cited peer-reviewed research. Most articles attributed change to anthropogenic causes, although ocean science articles addressing climate change were less likely to do so. Uncertain language and solutions were observed in nearly half of all articles. Optimistic language outnumbered doom and gloom language across all categories. While doom and gloom language was identified in 10% of all articles, optimistic language was present in 27%.